Treatment of an "ankylosed" upper central incisor in the mixed dentition - Cerny Robert (Sciendo, 2000)
A ten-year-old boy presented with an unerupted upper right central incisor (UR1). An OPG radiograph showed a super-numerary tooth lying over its crown, preventing its eruption. Standard orthodontic treatment involving removal of the super-numerary tooth, attaching a gold chain to the UR1 and treatment with fixed orthodontic appliances failed to bring the tooth down, until it was found that tough fibrous gingival tissue entwined in the gold chain had "ankylosed" the tooth. Once this tissue had been removed and the wound packed open, the tooth was brought down successfully into occlusion.